2003
DOI: 10.1530/reprod/125.5.717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal body condition on placental and fetal growth and the insulin-like growth factor axis in Dorset ewes

Abstract: This study investigated the effects of maternal body condition on fetal growth. Fetal and placental parameters from Dorset ewes of body condition score 2.0 (lean, n = 5), 3.5 (moderate, n = 7) and 5.0 (fat, n = 4) at mating were studied on day 65 of gestation. The fetal weight and fetal weight:crown-rump length ratio were greater in fat ewes than in ewes of moderate condition. The raised total and mean placentome weight in fat ewes compared with ewes of moderate condition may have contributed to their increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Therefore, there were opposite trends in closely adjacent maternal uterine tissues, which were presumably exposed to similar circulating hormone concentrations. In the Dorset ewe in mid gestation we have previously reported reduced expression of both IGFBPs-3 and -5 mRNA in the glandular epithelium of ewes of fat compared with thin body condition (Osgerby et al 2003a). Surprisingly little is known about local factors regulating IGFBP expression in different tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there were opposite trends in closely adjacent maternal uterine tissues, which were presumably exposed to similar circulating hormone concentrations. In the Dorset ewe in mid gestation we have previously reported reduced expression of both IGFBPs-3 and -5 mRNA in the glandular epithelium of ewes of fat compared with thin body condition (Osgerby et al 2003a). Surprisingly little is known about local factors regulating IGFBP expression in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have demonstrated that placentome proliferation reaches a maximum rate between days 50 and 60 of gestation, with placentomes attaining a maximum weight by days 75 to 80 (Ehrhardt & Bell 1995). Nutritional insults during this period have thus been associated with changes in placental growth (McCrabb et al 1992), with maternal factors including weight, age and body condition influencing this interaction (DeBarro et al 1992, Wallace et al 1997, Osgerby et al 2003a. In this study, placentome weight was not, at this early stage, influenced by nutrition although we have previously reported that the 70% reduction in ration did result in altered fetal growth by day 90, with more obvious signs of fetal growth retardation apparent by day 135 of gestation (Osgerby et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal plasma IGFs play a role in maternal tissue growth and metabolism, resulting in the modulation of nutrient availability for adequate conceptus growth and have been positively correlated with fetal growth in several livestock species (Sferruzzi-Perri et al, 2011). As a result, maternal plasma IGF-1 could potentially affect fetal growth indirectly and is itself altered by both BCS and diet during gestation (Osgerby et al, 2002(Osgerby et al, , 2003a.…”
Section: Resultsmentioning
confidence: 99%